Breakout : the Dred chronicles - Aguirre, Ann (Aguirre, Ann. Dred chronicles., 2015)
As the Dread Queen tries to end her "lifetime" stay on the prison ship Perdition, the Queenlanders must outwit and outsmart the enemy to gain their freedom and win a prize sweeter than their wildest dreams.